2012
DOI: 10.1016/j.jcin.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Provoked Exercise Desaturation in Patent Foramen Ovale and Impact of Percutaneous Closure

Abstract: One-third of patients referred for assessment of PFO experience oxygen desaturation during stair exercise. Closure of PFO seems to ameliorate this phenomenon and improve functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 12 publications
0
37
0
5
Order By: Relevance
“…The rationale for percutaneous device closure is supported by the work of Fenster et al ,8 Devendra et al 9 and El Tahlawi et al ,10 who reported significant symptomatic and functional status improvement in their respective cohorts with this therapy. The common denominator in their series was the absence of significant pulmonary hypertension in recipients of percutaneous closure devices.…”
Section: Treatmentmentioning
confidence: 97%
“…The rationale for percutaneous device closure is supported by the work of Fenster et al ,8 Devendra et al 9 and El Tahlawi et al ,10 who reported significant symptomatic and functional status improvement in their respective cohorts with this therapy. The common denominator in their series was the absence of significant pulmonary hypertension in recipients of percutaneous closure devices.…”
Section: Treatmentmentioning
confidence: 97%
“…(Sacco, 1997; Mas, 2001; Donnan & Davis, 2004; Furlan, 2004; Tong & Becker, 2004; Ferguson, 2006; Bedard, 2007; Belvis, 2007; Furlan, 2007; Messe & Kasner, 2008; Windecker & Meier, 2008; Mazzucco, 2009; Mattle, 2010; Calvert, 2011) While establishing the “proper treatment” is beyond the scope of this review and current data, this lack of clinical consensus likely originates from complexities of PFO-related injury itself, as a myriad of associated risks differ widely between individual patients, and further novel risk factors are just beginning to be recognized. (Yip, 1997; Petty, 1999; Jacobs, 2002; Schneider, 2004; Handke, 2007; Silver, 2007; Ning, 2008; Ning, 2009; Agarwal & Kapadia, 2010; Devendra & Krasuski, 2011; Haghikia, 2011; Lau, 2011; Petrea, 2011; Devendra, 2012; La Spina, 2012)…”
Section: Stroke and Pfomentioning
confidence: 99%
“…(Lovering, 2011) While this difference was not demonstrated during exercise in this particular study, another study showed that endovascular PFO closure improved exercise capacity and reduced exercise-induced hypoxemia. (Devendra & Krasuski, 2011) In this innovative study, “provoked exercise desaturation (PED)” was well characterized as “arterial desaturation during assessment of at least 8% to a value less than 90%” during ambulation up and down 4 flights of stairs. Of interest, one third of patients with PFO-related stroke had oxygen desaturation during stair exercise.…”
Section: Stroke and Pfomentioning
confidence: 99%
See 1 more Smart Citation
“…What has not been known but is nicely shown by Devendra et al (1) in this issue of JACC: Cardiovascular Interventions is that it may do so much more commonly than previously thought. What has not been known but is nicely shown by Devendra et al (1) in this issue of JACC: Cardiovascular Interventions is that it may do so much more commonly than previously thought.…”
mentioning
confidence: 93%